PENGARUH DAYA LEDAK OTOT TUNGKAI, KOORDINASI MATA TANGAN DAN KONSENTRASI TERHADAP KEMAMPUAN BLOCK BOLAVOLI - Fikri Asdi; Muhamad Sazeli Rifki (Jurnal Sporta Saintika, 2020)
ABSTRACK The problem in this study is (1) there are still many students who do not understand and are less able to block properly. (2) limited ability of teachers to train and explore students' potentials, (3) There is little or limited training time so that understanding and dexterity of basic techniques are not fully implemented. This type of research is quantitative research using path analysis techniques. This research was conducted in August 2019, this research was located at SMA Negeri 1 Lubuk Basung. The population in this study were students at SMA Negeri 1 Lubuk Basung from all classes X, XI, XII totaling 100 people. Samples were taken as many as 30 people with purposive sampling technique. Data was collected through assessment instruments namely Leg Muscle Explosion Power, Hand Eye Coordination, Concentration, Volleyball Block Skills. Data analysis techniques are descriptive and inferential using path analysis. Based on the analysis of research data obtained; (1) There is a direct effect of Leg Muscle Explosion Power on Volleyball Block Skills of 6.35%. (2) There is a direct influence of Hand Eye Coordination on Volleyball Block Skills of 11.56%. (3) There is a direct effect of Concentration on Volleyball Block Skills by 16.89%. (4) There is a direct effect of Leg Muscle Explosion Power on the concentration of 16.89%. (5) There is a direct effect of Hand Eye Coordination on the concentration of 35.16%. Based on the results of the study it can be concluded that most of the Volleyball Block Skills of extracurricular students at SMA Negeri 1 Lubuk Basung are found in the concentration variable.